PENGARUH BOARD GENDER DIVERSITY, BOARD INDEPENDENCE, CEO DUALITY DAN CEO TENURE TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI: THE INFLUENCE OF BOARD GENDER DIVERSITY, BOARD INDEPENDENCE, CEO DUALITY AND CEO TENURE ON COMPANY VALUE IN MANUFACTURING COMPANIES LISTED ON THE IDX - Ricky Rama Saputra; Gatot Nazir Ahmad; Destria Kurnianti (Yayasan Education and Social Center, 2023)
This study aims to investigate the influence of board gender diversity, board independence, CEO duality, and CEO tenure on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The independent variables in this study are board gender diversity, board independence, CEO duality, and CEO tenure, while the dependent variable is firm value, measured by the price to book ratio (PBV). The data used in this study consists of annual reports of manufacturing companies published by the IDX during the time period of 2016 to 2020. The number of samples used in this study were 94 companies with observations for 5 years so that 470 objects of observation were selected. The sampling method used in this study is purposive sampling, and the research analysis is conducted using panel data regression. The results of this study contrast with the theory of good corporate governance. The empirical result shows that Board Independence, and CEO Tenure had a significant and negative effect on firm value. While board gender diversity, and CEO duality do not influence the firm value